Improving the Quality of Education Through Quality of Service and Education Costs - Rangga Firdaus; Sunarno; Ahmad Fahmi; Fadhillah; Mowafg Masuwd (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The quality of education is a key measure of an educational institution's ability to produce high-achieving students. Such institutions must provide effective learning services and ensure education costs remain affordable and aligned with students' needs. This research adopts a quantitative approach, using statistical analysis to process data gathered through questionnaires. The results highlight that service quality (X1) and education costs (X2) have a significant and positive impact on education quality (Y), both independently and collectively. Specifically, the t-test reveals that the t-value for service quality (6.783) exceeds the t-table value (1.992), indicating a significant effect on education quality. Conversely, the t-value for education costs (1.808) falls below the threshold, suggesting no substantial impact. These findings emphasize that service quality is a critical driver of educational quality, while education costs have a less direct effect. The study advocates for prioritizing improvements in service quality, such as better teaching methods and resource availability, while efficiently managing education costs. These strategies are essential to enhancing the overall quality of education and ensuring better outcomes for students. This research provides actionable insights for educational policymakers and institutions aiming for sustainable improvement.